Electronic Payment and Economic Growth in Indonesia - Wasiaturrahma, Wasiaturrahma; Kurniasari, Anita Lucky (Universitas Airlangga, 2021)
The purpose of this study is to investigate the effect of non-cash payment transactions on economic growth in Indonesia and to see the responses from supporting variables, such as the velocity of money and the price of transactions. This study involves a Vector Error Correction Model (VECM) analysis tool, using monthly time series data during 2009: 1 – 2017: 12. The results show that the payment instrument affects economic growth, especially the Card-Based Payment Instrument (CBPI). In addition, there are changes to the velocity of money and prices caused by the increase in the use of non-cash payment instruments. Keywords: Electronic Payment, Economic Growth, Vector Error Correction Model (VECM)JEL: E4; C51